Supramolecular ethanol-water clusters in alcoholic beverages: Review on 2D correlation fluorescence and NMR spectral characterizations - Hui-Shuang Li; Hao-jie Bai; Yi Li; Yuqing Wu (Supramolecular Materials)
While the studies have revealed that the type and content of ingredients are crucial factors in determining the quality and taste of alcoholic beverages, the liquid-liquid condensed phase of the supramolecular network of ethanol-water clusters (E-Wc) have been demonstrated playing important influence either. The supramolecular clusters in alcoholic beverages, especially the intrinsic hydrogen-bondings (HBs) to organoleptic sensing and quality assessment, have gradually been elucidated recently. The veiling concealed on the supramolecular entities as a key proportion of the ethanol-water solution (E-Ws) starts to be disclosed with the discrete achievements in this research area. To build a full understanding of the cluster driving in versatile alcoholic beverages via unique techniques for characterization, this review summarizes the involved supramolecular E-Wc by fluorescence emission and NMR spectra. In particular, the two-dimensional correlation (2D-COS) analysis has been introduced as a powerful tool for characterizing the important structural profiles in clusters. With the help of carving important supramolecular E-Wc, it is hoped that the prospects and challenges in this field will be clearer and that such kinds of condensed liquid phases can possess the potential as supramolecular material additives to modulate the products with various tastes and quality in the alcoholic industry.